A geopolitical turn to EU enlargement, or another postponement? An introduction. Issue 2 (3rd April 2021) - Petrovic, Milenko; Tzifakis, Nikolaos
ABSTRACT: This article, which introduces a Special Issue of the JCES on the challenges of EU enlargement policy towards the Western Balkans, critically examines the geopolitical turn of the EU's institutional thinking on enlargement since 2017. After several high-ranked EU officials and leaders of member states more or less explicitly voiced their concerns about the declining influence of the EU in the Western Balkans, the European Commission – which has traditionally been responsible for carrying out administrative-technical aspects of the accession process – adopted a more geopolitical approach to enlargement policy in February 2018, and has since sought to advance Western Balkan accession more decisively. However, this geopolitical turn to the EU's institutional thinking on enlargement has so far failed to translate discourse into concrete results. The article argues that the main reasons for this failure can be found in a lack of support by EU members, which either do not share the Commission's sense of urgency, or are eager to use enlargement policy and the accession process to advance their national interests. The article concludes with a brief presentation of the structure of the special issue and introduces the contributing articles.